Pembagian Harta Bersama Perkawinan Dalam Perceraian Perkawinan Beda Agama Yang Dicatatkan - erma kartika timur (Trunojoyo Madura University, 2017)
Interfaith marriage in Indonesia be able to do with supplicate a determination to District Court, and then be listed in the Civil Registry Office. In case divorce occur on registered interfaith marriages, there is legal vagueness in regulation to divide joint property marriage, its relates with article 37 Constitution Number 1 of 1974 about Marriage. The purpose of this thesis is to description, identifying and analyzing the way to divide marriage property in interfaith marriage divorce, and also to review allowed or not to make choice of law that related to article 37. This thesis is a normative research with using statute approach and analytical approach. Based on the analysis of legal materials obtained, solution to divide joint property marriage on interfaith marriage better used husband religion or customary law, it is based from analysis using intergroups legal theory, receptive in complex theory, Idris Ramulyo opinion, Lanraad jurisprudence in Manado and also using grammatical interpretation about husband and wife position in article 31 and 34 marriage law. In case lawsuit happened, there is through the District Court after divorce decision was decided by judges. Choice of law is allowed based on equally principle.